BIOLOGICAL ACTIVITIES OF ALTERNARIA SP. RL4 – A POTENT ENDOPHYTIC FUNGUS ASSOCIATED WITH RAUVOLFIA SERPENTINA L. BENTH. - Ghosh, Ranjan; Barman, Soma; Jgs, Pavan Kumar; Mandal, Narayan C (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Endophytic fungi are considered as an important source of bioactive metabolites. The present study focused on the isolation of potent endophytic fungal strains from well-known medicinal plant Rauvolfia serpentina L. Benth. having biological activities. Materials & Methods: Fungal endophytes were isolated from aerial parts of the plant and the potent strain was selected on the basis of antibacterial activities of cell-free supernatant (CFS). Ethyl acetate (EA) extraction of CFS was done and mode of action of EA fraction was checked against pathogenic bacteria. EA fraction was also analyzed by thin-layer chromatography (TLC). In addition, antioxidant activity was checked by 1,1-Diphenyl- 2-picrylhydrazyl-free radical scavenging assay and anticancer activity was checked against breast cancer cell line MCF-7 by MTT assay. Results: Among the different endophytic fungal isolates, CFS of Alternaria sp. RL4 produced prominent zones of inhibition against numbers of Gram-positive pathogenic bacteria including Staphylococcus aureus (12±0.5 mm) and Listeria monocytogenes (17±2.0 mm). Massive reductions in bacterial CFS were noticed upon treatment with EA fraction (2 mg/ml). It also showed strong cidal mode of action against Gram-positive organisms. TLC analysis revealed the production of two different compounds with antibacterial potentials. In addition, EA fraction of RL4 showed very good antioxidant property with an IC50 value of 49.80±2.11μg/ml. MTT assay also suggested the anticancerous properties of EA fraction of RL4. Conclusion: Alternaria sp. RL4 could be a very good source of bioactive compounds for the development of new drugs.